Preferences in the Intention to Download a COVID Tracing App: A Discrete Choice Experiment Study in the Netherlands and Turkey - Folkvord, Frans; Peschke, Lutz; Gümüş Ağca, Yasemin; van Houten, Karlijn; Stazi, Giacomo; Roca-Umbert, Ana; Güneş Peschke, Seldağ; Seyfafjehi, Seyedehshahrzad; Gallego, Alba; Gaeta, Eugenio; Fico, Giuseppe; Karinsalo, Anni; et al. (Frontiers in Communication, 2022)
Introduction: High levels of adoption and usage for the Covid Tracing Apps (CTA) among the population is a stipulated prerequisite for success of the implementation of these apps, aiming to mitigate the pandemic and track spreading of the virus more efficient and effectively. In the current study, the main objective was to investigate individuals’ preferences in the intention to download a COVID-19 tracing app in a pilot-study in both the Netherlands and Turkey. Methods: We conducted a discrete choice experimental study through an online survey in two countries (the Netherlands [N=62] and Turkey [N=83]), with four different attributes: 1) data protection (data protection vs. no information), 2) manufacturer (government vs. company), 3) reward (no reward vs. voucher as a reward) and 4) gaming (no gaming elements vs. gaming elements). Participants were recruited among a student population. Results: The results showed that data protection is one of the most important factors that significantly increases the probability to adopt a CTA. In general, the manufacturer, reward or gaming affected the probability to download the CTA less. Discussions: Health authorities worldwide have generally released high quality CTA, although scientific studies assessing the most important factors that describe and predict the intention to download is limited. Sensitive personal data is collected through these apps, and may potentially threaten privacy, equality and fairness, which are important attributes to take into account when developing or launching a CTA, following the results of this study.